Relationship between transfer activity coefficients, (S(1))γ(S(2)), of cryptate 2.2.2 complexes and their stability constant in various solvents - Kolthoff, Izaak M. (1980)
Between dipolar aprotic solvents S(1) and S(2), the transfer activity coefficients, (S(1))γ(S(2)), of complexed sodium, potassium, thallium(I), and silver ions with cryptand 2.2.2 have been found to be equal to that of the cryptand. With reference to methanol (S(1)), this equality does not hold, the cryptates being more or less solvated by hydrogen bonding in this solvent. In water as a solvent, the cryptates are on a considerably higher level of free energy than in the organic solvents. This is attributed to hydrophobic hydration of the cryptates.